Razvoj digitalnih kompetenc in ustvarjanje digitalnih vsebin pri pouku slovenščine v 8. razredu s sodelovalnim delom pri Županovi Micki - Vidovič, Janja (Revija inovativna pedagogika, 2025)
The article focuses on how collaborative work and a project-based approach in Slovenian language classes can enhance pupils' digital competencies, particularly in digital content creation. This paper aims to present the potential of active pupil engagement and collaborative learning while simultaneously developing digital competencies in the Grade 8 Slovenian curriculum, specifically within the unit on Enlightenment drama, using Anton Tomaž Linhart's comedy Županova Micka as the central literary work. Throughout the process, special attention was given to developing digital competencies from 3.1, Digital Content Creation, up to level 4, as defined by the DigComp 2.2 framework. Data were collected qualitatively through observation, monitoring, and group work reflection. The descriptive method is used in this article, focusing on a detailed account of observed findings. This article is primarily intended for subject teachers seeking innovative and contemporary teaching methods that emphasize learner-centered project work, fostering digital literacy, strengthening team spirit through collaborative work, and promoting critical thinking. It also addresses the broader professional community engaged in exploring active learning methodologies and the integration of digitalization into educational practices.
Keywords: collaborative learning; digital competencies; Digitalna pismenost; digitalne kompetence; innovative teaching methods; inovativne metode poučevanja; Osnovnošolsko izobraževanje; project-based learning; projektno delo; Slovenščina; sodelovalno delo